2006
DOI: 10.1038/sj.jid.5700016
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance Induction by the Blockade of CD40/CD154 Interaction in Pemphigus Vulgaris Mouse Model

Abstract: Pemphigus vulgaris (PV) is an autoimmune blistering disease caused by IgG autoantibodies against desmoglein 3 (Dsg3). We have recently developed an active disease mouse model for PV by adoptive transfer of splenocytes from Dsg3 À/À mice. The purpose of this study was to determine the role of CD40/CD154 interaction in the pathogenic antibody production and development of the disease in PV model mice. When anti-CD154 monoclonal antibody (mAb) was administered to recipient mice prior to adoptive transfer, anti-CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 40 publications
4
29
0
Order By: Relevance
“…55 Besides, the blockade of the CD40-CD40L interaction by treatment with anti-CD40L monoclonal antibody inhibited the production of anti-Dsg3 IgG as well as the development of the pemphigus vulgaris disease phenotype in a mouse model. 6 In summary, our results reveal that CD40L, CD40 and BLYS are important genes modulating the susceptibility to endemic PF. Slight influence, like we saw for CD40À1C4T and BLYSÀ871C4T SNPs individually, is the rule in complex diseases.…”
Section: Expression Of Cd40l On T Cells Is Transient With the Ligandmentioning
confidence: 96%
See 1 more Smart Citation
“…55 Besides, the blockade of the CD40-CD40L interaction by treatment with anti-CD40L monoclonal antibody inhibited the production of anti-Dsg3 IgG as well as the development of the pemphigus vulgaris disease phenotype in a mouse model. 6 In summary, our results reveal that CD40L, CD40 and BLYS are important genes modulating the susceptibility to endemic PF. Slight influence, like we saw for CD40À1C4T and BLYSÀ871C4T SNPs individually, is the rule in complex diseases.…”
Section: Expression Of Cd40l On T Cells Is Transient With the Ligandmentioning
confidence: 96%
“…In vivo blockade of CD40 or CD40L suppresses the induction of autoimmune diseases in murines (for a review, see Howard and Miller 5 ), including in pemphigus vulgaris model mice. 6 Therefore, blockade of the CD40-CD40L interaction has been considered an attractive immunoregulatory strategy for the suppression of antibody production in autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the blockade of the pathway by anti-CD40L antibodies has ameliorated the clinical and laboratory parameters of nephritis in both mice [17,18,19,20] and humans [21]. Furthermore, it is of note that anti-CD40L antibody has recently been proved to be effective in a mouse PV model [22]. …”
Section: Introductionmentioning
confidence: 99%
“…CD40L (CD154) binding on activated T cells with CD40 on B cells is considered critical to the interaction of activated T and B cells. It has also been shown that anti-CD154 mAb is capable of blocking this interaction between CD40 and CD154, resulting in the suppression of anti-Dsg3 IgG production [85]. Future investigations into autoreactive T-cell regulators of B-cell antibody production are needed to shed light on more targeted therapeutic interventions.…”
Section: T-and B-cell Regulationmentioning
confidence: 99%